Metode Mediasi dalam Penyelesaian Sengketa Tanah untuk Mewujudkan Penyelesaian Sengketa yang Efisien dan Berkepastian Hukum - Albanjari, Muhammad Kissan; Zubaedah, Rahmi (Jurnal Ilmiah Wahana Pendidikan, 2024)
The increase in land cases in court has raised the desire to speed up the settlement process through out-of-court settlement patterns, besides that the settlement of land disputes in court has many drawbacks including being very bureaucratic and time-consuming and quite a lot of money. Based on the Regulation of the Minister of Agrarian Affairs and Spatial Planning/Head of the National Land Agency No. 11 of 2016 concerning the settlement of land cases, land disputes can be resolved through mediation outside the court. The mediation model that is suitable for resolving land disputes is interest-based mediation, namely the focus of mediation is directed at the substance of the best interests of both parties based on aspects of joint resolution by resolving the root of the problem, avoiding prolonged conflict between the parties, and the desire to have a good long-term relationship. Studying and handling land cases which is the duty of all levels of society in assisting the National Land Agency's task of resolving land cases can be resolved quickly